Macierzowa Analiza Statyczna Płaskich Rusztów Kołowych - G. Rakowski (Engineering Transactions)
Application of the method of transfer matrix is described for the static analysis of a grid arbitrarily supported on its ends and elastically in intermediate nodes, arbitrarily loaded. The basics matrices essential for making calculations have been constructed. Simple, systemized calculations can be readily performed by means of computers.